2008
DOI: 10.1097/wnr.0b013e3282f2dff6
|View full text |Cite
|
Sign up to set email alerts
|

Associative learning in deficit and nondeficit schizophrenia

Abstract: When two stimuli are associated and treated as equivalent, generalization occurs between them (acquired equivalence). The feedback-guided learning of associations is related to the basal ganglia, whereas the medial temporal lobe participates in acquired equivalence learning. In this study, we investigated feedback-guided associative learning and acquired equivalence in deficit and nondeficit schizophrenia. Results revealed that acquired equivalence learning was similarly impaired in deficit and nondeficit pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
4
29
1
Order By: Relevance
“…The present findings thus complement previously reported data demonstrating impaired hippocampal-dependent generalization in schizophrenia [4, 30, 31], and extend these prior observations by demonstrating that generalization is sensitive to modulation by anti-psychotic medication. This raises important questions regarding the cause of generalization deficits in schizophrenia, as well as the mechanism by which anti-psychotic medication may impact generalization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings thus complement previously reported data demonstrating impaired hippocampal-dependent generalization in schizophrenia [4, 30, 31], and extend these prior observations by demonstrating that generalization is sensitive to modulation by anti-psychotic medication. This raises important questions regarding the cause of generalization deficits in schizophrenia, as well as the mechanism by which anti-psychotic medication may impact generalization.…”
Section: Discussionsupporting
confidence: 92%
“…There has been one previous report that medication dose in schizophrenia correlated with number of errors in the learning phase of a task similar to the one used here [30]. However, we found neither an effect of medication on learning phase performance, nor a correlation with medication dose, consistent with a more recent report [31]. This difference may be related to the overall higher APD doses tested in that study [30], compared to the present one.…”
Section: Discussionsupporting
confidence: 81%
“…Neuropsychological investigations reported discrepant findings, with some studies reporting a greater impairment in DS than in NDS on measures of fronto-parietal functions (i.e., attention, executive control and visuospatial functions, Buchanan et al, 1994;Bryson et al, 2001;Yu et al, 2015), prefrontal functions (verbal fluency, concept formation and cognitive flexibility, Cascella et al, 2008;Polgár et al, 2010) or cortico-striatal functions (reinforcement learning, Farkas et al, 2008;Polgár et al, 2010;Vogel et al, 2013). The majority of studies (Galderisi et al, , 2013aWang et al, 2008;Polgár et al, 2008;Réthelyi et al, 2012;Fervaha et al, 2015a) and a meta-analysis (Cohen et al, 2007) reported a generalized cognitive impairment in DS vs both NDS and controls.…”
Section: Neurocognitive Impairmentmentioning
confidence: 96%
“…Additionally, it has been shown that different WM tests require varying amounts of executive function and research using factor analytic approach demonstrated that FDS and BDS tasks load together to form a factor separate from other tests with higher central executive WM demands, such as N-back task (Allen et al, 2010). Farkas et al (2008) found that schizophrenia patients with severe negative symptoms are more impaired at rule learning tasks than schizophrenia patients with milder negative symptoms.…”
Section: Discussion Different Domains Of Wm With Respect To Psychosismentioning
confidence: 97%